Concepts in solids : lectures on the theory of solids - Anderson, P. W. (Philip W.), 1923-2020. (Singapore ; River Edge, NJ : World Scientific, 1997)
These lecture notes constitute a course on a number of central concepts of solid state physics - classification of solids, band theory, the developments in one-electron band theory in the presence of perturbation, effective Hamiltonian theory, elementary excitations and the various types of collective elementary excitation (excitons, spin waves and phonons), the Fermi liquid, ferromagnetic spin waves, antiferromagnetic spin waves and the theory of broken symmetry. The book can be used in conjunction with a survey course in solid state physics, or as the basis of a first graduate-level course. It can be read by anyone who has had basic grounding in quantum mechanics.
1. Introduction. A. Preparation and texts. B. Plan of the course. C. Generalities and classification of solids -- 2. One-electron theory. A. Hartree-Fock theory. B. Energy bands in solids. C. One-electron band theory in the presence of perturbing fields -- 3. Elementary excitations. A. The idea of elementary excitations: generalities on many-body theory. B. The N + 1 body problem. C. Quasi-particles in metals: the fermi liquid. D. Collective excitations.
Originally published: New York : W.A. Benjamin, 1963, in series Frontiers in physics. Reissued with special preface: Redwood City, Calif. : Addison-Wesley, 1992, in series Advanced book classics.
Includes bibliographical references (pages 183-188).
Print version record.
English.
eBooks on EBSCOhost
Keywords: Energy-band theory of solids; Electronic excitation; Excitation électronique.; Bandes d'énergie (Physique); SCIENCE -- Physics -- Condensed Matter; Electronic excitation; Energy-band theory of solids